Making Sense of the Future - Szostak, Rick (Taylor & Francis, 2022)
Making Sense of the Future integrates the latest thinking in Future Studies with the author's expertise in world history, economics, interdisciplinary studies, knowledge organization, and political activism. The book takes a systems approach that recognizes the complexity of our world. It begins by suggesting a set of goals for human societies and identifying innovative strategies for achieving these goals that could gain broad support. Each chapter begins with a "How to" section that discusses how we can identify goals, strategies, trends, surprises, or implementation strategies and concludes with an integrative analysis that draws connections across the preceding discussions. Taking a cross-disciplinary approach, Szostak explores key trends and how these interact so that he can develop strategies to guide trends towards desirable futures. He discusses the ways in which we can best prepare for surprises such as epidemics and natural disasters, enabling us to react to them in beneficial ways. Supported by a list of guiding questions and suggestions for class projects, this is an accessible textbook for students of Future Studies and Future Studies courses.